Characterization of environmental and clinical antibiotic-resistant Escherichia coli isolates - Filipe, Daniel Fernandes Magalhães (2022)
The rapid spread of antibiotic resistance among human pathogenic bacteria has been a global public health problem, expanding in recent decades. Antibiotic resistance genes found in clinical pathogens are not the only cause for concern, as it is recognized that commensal and environmental bacteria, as well as their mobile genetic elements, can function as reservoirs and vectors of resistance, and can spread genes through horizontal transfer and selection. The conjugation process is the horizontal gene transfer mechanism considered to be the most relevant in resistance spread. It is thought that the spread of resistance genes can be enhanced in the presence of various substances such as metal salts or antibiotics. Knowing the conditions under which mobilization takes place is crucial to control resistance spread. This study aimed to compare Escherichia coli isolates from clinical, wastewater and surface water samples (n=52), in order to assess if resistance profiles were source-dependent. A second objective was to understand if the rate and profile of antibiotic resistance gene transfer differed depending on the conjugation temperature. This work involved phenotypic and genotypic characterization and detection of resistance genes, as well as conjugation assays between a carbapenem resistant strain and a reference receptor. Specifically, susceptibility to different classes of antibiotics was determined by the disk diffusion method, PCR detection of antibiotic resistance genes and types of replicons present in plasmids was performed. In the conjugation assays, different temperatures were tested (25, 28, 35 and 40ºC), the transconjugants were selected in the presence of azide and ceftazidime, confirmed by genotyping and characterized for the presence of specific genetic determinants. Genotypic and phenotypic characterization of isolates identified as E. coli did not reveal significant differences (p>0.05) between environmental and clinical isolates, with the exception of IncF-type replicon plasmids, which were significantly (p0.05) between the rates observed at different temperatures. The transmission of the IncN plasmid holding the blaKPC gene was detected in all transconjugants analysed. However, the transmission of the FIBtype replicon was higher at conjugation temperatures of 35 and 40ºC than at 25 and 28ºC.